Utility of Bronchoalveolar Lavage in the Diagnosis of Sputum Negative Pulmonary Tuberculosis - Dhakal, Subodh Sagar; Neupane, Ashmita; Chaudhary, Shatdal; Mishra, Navin; Karki, Damber Bdr (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION: Sputum smear examination for acid fast bacilli (AFB) by Ziehl-Neelsen stain (ZN stain) is the initial approach to the diagnosis of pulmonary tuberculosis (PTB). But 50% of the cases are reported to be sputum smear negative. This study was aimed to investigate the diagnostic yield of fibreoptic bronchoscopy (FOB) guided bronchoalveolar lavage (BAL) in patients suspected to have tuberculosis. The sample was tested for Mycobacterium tuberculosis using the XpertMTB/RIF assay, which is a new test that detects Mycobacterium tuberculosis complex and resistance to rifampin in less than two hours. MATERIAL AND METHODS: This is a prospective cross sectional study carried out on 58 sputum smear negative patients who were clinically suspected to have pulmonary tuberculosis from April 2017 to January 2019. All patients are subjected to FOB, BAL and BAL specimens were stained for AFB and also sent for Xpert (MTB)/RIF. RESULTS: Among 58 patients enrolled for the study 26 patients were positive for acid fast bacilli (AFB) through BAL stain and Xpert (MTB)/RIF combined. CONCLUSION: FOB guided BAL is a reliable, alternative and rapid method for diagnosing smear negative pulmonary tuberculosis with minimal complications.